Autophagy-induced tumor dormancy in ovarian cancer - Amaravadi, Ravi K. (American Society for Clinical Investigation, 2008)
Autophagy — a process of “self-eating” that involves enzymatic digestion and recycling of cellular constituents in response to stress — contributes to both cancer cell death and survival. In this issue of the JCI, Lu et al. report that controlled induction of tumor suppressor gene aplasia Ras homolog member I (ARHI) results in autophagic cell death of human ovarian cancer cells in vitro (see the related article beginning on page 3917). However, within xenograft tumors in mice, multiple factors within the tumor microenvironment switched ARHI-induced autophagy to a mechanism of tumor cell survival, leading to tumor dormancy. Since ARHI expression is suppressed in the majority of breast and ovarian cancers but is high in premalignant lesions, ARHI-induced autophagy could be manipulated for therapeutic benefit.